A review on recent advances in CO2 separation using zeolite and zeolite-like materials as adsorbents and fillers in mixed matrix membranes (MMMs) - Moustafa M. Zagho; Mohammad K. Hassan; Majeda Khraisheh; Mariam Al Ali Al-Maadeed; Sergei Nazarenko (Chemical Engineering Journal Advances, 2021)
Anthropogenic emissions have developed the environmental demands for proficient carbon dioxide (CO2) separation technologies. Adsorption and membrane technologies are widely used to separate CO2 from other light gases due to their multiple technological benefits, including but not limited to factors such as energy efficiency and low environmental footprint. In this context, zeolites are often used due to their intrinsic molecular sieving capacity. This review initially addresses recent technological advances to enhance the gas separation performance of zeolite materials. Current trends directed toward improving CO2 adsorption capacity of zeolites include amine, silica, and ion-exchange modifications. Other promising efforts to improve the adsorption performance of zeolites involve processing zeolite nanoparticles, nanofibers, and zeolite-based foams. The second part of the review deals with pristine and modified zeolites beneficial properties for designing polymer-based mixed matrix membranes (MMMs), which enable to adapt a desirable gas separation performance. The gas transport mechanisms and morphological properties of MMMs are essential. This review addresses the most current strategies used to improve interfacial adhesions between zeolite particulates and polymer matrices to overcome the trade-off between gas selectivity and permeability faced by pure polymeric membranes. Filler shape and size play vital roles in determining the filler and polymer matrix's interfacial adhesions. New structures of inorganic fillers have been designed to fabricate MMMs with excellent gas transport properties. Hollow zeolite spheres (HZSs) are particularly interesting as they effectively minimize agglomeration and improve filler dispersion in the polymer matrix. Furthermore, approaches that employ nanoporous layered fillers, including AMH-3 and Jilin-Davy-Faraday, layered solid No. 1 (JDF-L1), have been reviewed to overcome the limitation of incorporating high contents of zeolites, which are required to improve the gas transport properties of MMMs. Furthermore, this review explores implementing zeolitic imidazolate frameworks (ZIFs) in MMMs because of their tunable pore structure and remarkably high adsorption capacity and surface area as well as excellent chemical and thermal properties. Lastly, we address the prospects and future developments in gas separation applications.